Efeito do canabidiol no reparo de úlceras mecanicamente induzidas na mucosa oral de ratos : avaliação clínica e histológica - Klein, Mariana (2018)
Ulcerative lesions are some of the most common injuries of the oral mucosa. Damage to the epithelial barrier results in discomfort, which may interfere with oral hygiene, chewing, swallowing and speech. The management of these lesions basically aims to optimize and accelerate tissue repair, in addition to reducing its symptomatology. However, there is no option considered gold standard for the treatment of traumatic mouth ulcers. Cannabidiol (CBD) is the main non-psychomimetic component of Cannabis sativa. It exerts potent antiinflammatory, antioxidant and analgesic effects when tested in various pathological conditions. The present dissertation is structured in the form of 2 scientific papers. The first article consists of a literature review to evaluate the different mechanisms of action of CBD that may be involved in the repair of ulcerative lesions, suggesting that this drug is promising for the treatment of oral inflammatory disorders. The second article is a report of an experimental study conducted in an animal model, to assess the effect of 5 and 10 mg/kg CBD on the repair of an ulcerative lesion induced on the ventral tongue of 60 Wistar rats after 3 and 7 days. Treatment with CBD decreased inflammatory scores after 3 days (p < 0.05), but was unable to clinically influence the size of ulcerative lesions. Thus, it is concluded that CBD has an inflammation modulating effect and may represent a promising alternative in the management of oral wounds.